2014
DOI: 10.1002/lt.23888
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative complications in liver transplantation using donation after cardiac death grafts: A propensity-matched study

Abstract: Donation after cardiac death (DCD) is an important source for expanding the donor pool for liver transplantation (LT).Although the long-term outcomes of LT using DCD grafts have been extensively studied, perioperative complications related to DCD grafts are rarely reported. The aim of this study was to determine whether DCD grafts were associated with a higher incidence of postreperfusion complications and worse outcomes in adult LT patients. After institutional review board approval, the medical records of al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 32 publications
1
38
0
Order By: Relevance
“…A previously published study with a smaller number of DCD patients (n = 74) showed similar PRBC and FFP transfusions in the postreperfusion period between DCD and DBD liver graft recipients. Also, the total volume of transfusion was less in both groups . When comparing our data to the aforementioned study, the current study had more DCD recipients, and the average numbers of products given per patient in both groups in the current study was less, making it difficult to draw a comparison between the 2 studies.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…A previously published study with a smaller number of DCD patients (n = 74) showed similar PRBC and FFP transfusions in the postreperfusion period between DCD and DBD liver graft recipients. Also, the total volume of transfusion was less in both groups . When comparing our data to the aforementioned study, the current study had more DCD recipients, and the average numbers of products given per patient in both groups in the current study was less, making it difficult to draw a comparison between the 2 studies.…”
Section: Discussionmentioning
confidence: 61%
“…A previous small study demonstrated a higher incidence of intraoperative events (PRS, hyperkalemia, and cardiac arrest) in recipients of DCD liver grafts compared with recipients of DBD liver grafts. (4) The present study aims to provide the largest and most detailed analysis to date of intraoperative events in LT using liver grafts from DCD compared with DBD donors.…”
mentioning
confidence: 99%
“…An important link between IRI and PRS is similarly accounted by Pan et al[104] in their retrospective study, where they report a double incidence of PRS in DCD compared to DBD (25.7% vs 12.2%, respectively). These authors also suggest that the severe IRI experienced by DCD grafts during the additional warm ischaemia occurring before organ procurement may play a role in the development of PRS.…”
Section: Specific Intra-operative Risk Factors For Post-lt Prs-inducementioning
confidence: 74%
“…PNF was defined as graft failure without secondary causes, leading either to retransplantation or death within the first posttransplant week. Early allograft dysfunction (EAD) was defined according to Olthoff et al Postoperative acute kidney injury (AKI) was defined according to the Risk, Injury, Failure, Loss and End‐Stage Kidney Disease criteria, and the need for continuous renal replacement therapy (CRRT) was also considered . Biliary complications included anastomotic and nonanastomotic biliary strictures, bile leaks, cholangitis, biliary casts, and stones requiring intervention or surgery .…”
Section: Methodsmentioning
confidence: 99%